1962
DOI: 10.1121/1.1918241
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Sound Waves

Abstract: Exact solutions for the interaction between two concentric cylindrical waves and between two concentric spherical waves are presented. The scattered-pressure amplitude in the far field is shown to be constant in the cylindrical case and to be proportional to r−1 lnr in the spherical case, where r is the distance to the source of primary waves. A near-field solution is derived for the scattered waves generated when two sharply defined, plane-wave beams of square cross section intersect at right a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…For spherically symmetric interacting waves, our analytic solution is exact and reduces to Baxter's [33] for this special case, where we show that Baxter's solution satisfies the Sommerfeld radiation condition but Dean's [29] does not. Analytic solutions are derived for the second-order field due to the interaction of a plane and spherical wave.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…For spherically symmetric interacting waves, our analytic solution is exact and reduces to Baxter's [33] for this special case, where we show that Baxter's solution satisfies the Sommerfeld radiation condition but Dean's [29] does not. Analytic solutions are derived for the second-order field due to the interaction of a plane and spherical wave.…”
Section: Discussionmentioning
confidence: 94%
“…Equation (90) reduces exactly to Baxter's solution [33]. Compared to Baxter's solution, it is found that Dean's earlier solution [29] has an extra term proportional to the spherical Bessel function j 0 (k ± r) so violates the Sommerfeld radiation condition (online supplementary material). A further approximation made by Dean for the far field k ± r 1 and a small object k ± a 1, however, satisfies the Sommerfeld radiation condition because it contains only the dominant e ik±r log(k ± r)/r term.…”
Section: Scattered-scattered Interactionmentioning
confidence: 97%
See 2 more Smart Citations
“…This configuration creates beams that start to spatially interact very near the transducer surface. These ultrasound waves interact with each other and this phenomenon is known as scattering sound by sound or parametric mixing, which has been explored by Thuras, Westervelt, and others [23-26]. When two sound waves of different frequencies propagate together in a nonlinear medium, additional acoustic waves are produced at harmonics of the two original waves (2 f 1 , 2 f 2 ) as well as at the sum ( f 1 + f 2 ) and difference ( f 1 − f 2 ) frequencies of the two different frequencies [27].…”
Section: Methodsmentioning
confidence: 99%